The battle of the Labyrinth - Riordan, Rick (2008)
"Percy Jackson isn't expecting freshman orientation to be any fun. But when a mysterious mortal acquaintance appears on campus, followed by demon cheerleaders, things quickly move from bad to diabolical. In this latest installment of the blockbuster series, time is running out as war between the Olympians and the evil Titan lord Kronos draws near. Even the safe haven of Camp Half-Blood grows more vulnerable by the minute as Kronos's army prepares to invade its once impenetrable borders. To stop them, Percy and his demigod friends must set out on a quest through the Labyrinth--a sprawling underground world with stunning surprises at every turn. Full of humor and heart-pounding action, this fourth book promises to be their most thrilling adventure yet."--Publisher's description
I battle the cheerleading squad -- The underworld sends me a prank call -- We play tag with Scorpions -- Annabeth breaks the rules -- Nico buys happy meals for the dead -- We meet the God with two faces -- Tyson leads a jailbreak -- We visit the Demon Dude Ranch -- I scoop poop -- We play the game show of death -- I set myself on fire -- I take a permanent vacation -- We hire a new guide -- My brother duels me to the death -- We steal some slightly used wings -- I open a coffin -- The lost God speaks -- Grover causes a stampede -- The council gets cloven -- My birthday takes a dark turn
Accelerated Reader AR
Reading Counts
Lexile
F&P
Keywords: Jackson, Percy -- (Fictitious character) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Labyrinths -- Juvenile fiction; Camps -- Juvenile fiction; Monsters -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Children's stories, American -- 21st century; Young adult fiction; Fantasy fiction; Fantasy fiction; Juvenile literature